LEGAL THEORY IN THE APPLICATION OF INDONESIAN LAW - Muhammad Edi Suharyanto; Suparnyo (INTERNATIONAL JOURNAL OF SOCIETY REVIEWS, 2024)
The position of theory is very important in science, this can be seen from the task of theory, namely deepening the problem being studied. The existence of a theory can strengthen what previously stood alone, so that they reinforce each other and questions that are not yet clear are explored more deeply. In any field that is a field of legal science, theory can be a practical guide that explains how to approach the subject matter to be studied. Legal theory generally follows the flow of positive law, namely the search for just law. Law is an order issued by a sovereign authority, addressed to the government and given sanctions if violated (Austin). Pure law is a necessity that regulates human behavior as intelligent creatures (Kalsen). The application of legal theory emphasizes that a positive legal system will operate effectively if it follows the rules and norms of society. The combination of the three judges, certainty theory and utility theory is the right way to apply it in Indonesia.